2020
DOI: 10.1002/cplu.202000653
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ammonium Terephthalate Salts with High Moisture Resistance and Their Use in the Detection of OH Radicals

Abstract: A novel and practical method is proposed for the detection of gaseous OH radicals using a moisture‐resistant organic salt composed of terephthalic acid (TPA) and n‐alkylamine. When the alkyl chain length was greater than 8, the organic salt had a crystal structure in which the alkyl chains were arranged parallel to each other and zero‐dimensional voids were adjacent to terephthalate (TA). Since the parallelly arranged alkyl chains acted as a hydrophobic block, the organic salts had excellent humidity durabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Three kinds of free radical quenching agents, i.e. , p -benzoquinone as an ˙O 2 − quenching agent, 51 isopropyl alcohol as an ˙OH quenching agent, 52 and tryptophan as an 1 O 2 quenching agent, 53 were applied to the Tar-IrNPs catalysis system, and the changes in absorbance were recorded. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three kinds of free radical quenching agents, i.e. , p -benzoquinone as an ˙O 2 − quenching agent, 51 isopropyl alcohol as an ˙OH quenching agent, 52 and tryptophan as an 1 O 2 quenching agent, 53 were applied to the Tar-IrNPs catalysis system, and the changes in absorbance were recorded. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Free radical quenching experiments were subsequently performed to explore the possible involvement of reactive oxygen species (ROS) in the Tar-IrNPs catalyzed oxidation of PPD. Three kinds of free radical quenching agents, i.e., p-benzoquinone as an O 2 À quenching agent, 51 isopropyl alcohol as an OH quenching agent, 52 and tryptophan as an 1 O 2 quenching agent, 53 were applied to the Tar-IrNPs catalysis system, and the changes in absorbance were recorded. As shown in Fig.…”
Section: The Catalytic Mechanism Of Tar-irnpsmentioning
confidence: 99%
“…In n-alkylammonium terephthalate crystals with alkyl chain lengths longer than 8, the alkyl chains are packed closely with all-trans zigzag conformations and aligned parallel to each other. 32) Longer alkyl chain lengths enhance van der Waals interactions between alkyl chains, and thus strengthen the packing between them. [33][34][35] It is likely that the stronger packing between alkyl chains limited the penetration of OH into the crystal, and reduced the efficiency of the reaction of TA with OH to form HTA, resulting in lower n b .…”
Section: Relationship Between Alkyl Chain Length and Fluorescence Res...mentioning
confidence: 99%
“…Furthermore, we succeeded in immobilizing nOA-TA nanocrystals uniformly on a membrane filter by a simple dipping and drying process, and demonstrated that the spatial distribution of gaseous OH can be visualized as the HTA fluorescence intensity distribution by using this sheet as an OH detection sheet. 32) We believe that n-alkylammonium terephthalates with alkyl chain lengths longer than 8, such as nOA-TA, are ideal solid scavengers for gaseous OH because of their high moisture resistance. The sheets on which they are immobilized are easily fabricated and highly portable, enabling application for on-site OH measurements in various processes.…”
Section: Introductionmentioning
confidence: 99%